Control process for homogenization of high-strength tire cord steel structure

By adjusting the weight ratio of manganese to molybdenum and multi-pass heating and rolling process, the problems of cord steel structure unevenness and low soxantia ratio are solved, and the tensile strength and service life of cord steel are significantly improved.

CN119824192APending Publication Date: 2025-04-15XINJI AOSEN STEEL GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094384.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the traditional cord steel preparation process, the structural unevenness of the steel leads to stress concentration, which reduces the strength and toughness of the cord steel, and the low sonitite rate affects the overall performance of the steel.

Method used

By adjusting the weight ratio of manganese to molybdenum to 1~2:1, and using multiple passes of heat treatment and rolling processes, including rough rolling, finishing rolling and reduced diameter, the pressure rate of each pass is controlled, and the structural uniformity and soxantia rate of cord steel are improved.

Benefits of technology

It significantly improves the tensile strength and tissue uniformity of cord steel, extends the service life, reduces the frequency of maintenance, and improves the overall performance of steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, and provides a high-strength tire cord steel structure homogenization control process which comprises the following steps: S1, heating a steel billet to obtain a heated steel billet; s2, the heated steel billet is rolled, spun and cooled, and tire cord steel is obtained; the rolling process comprises 3-8 passes of rough rolling, 10-13 passes of finish rolling and 2-6 passes of reducing sizing; and during finish rolling, the reduction rate of the first five passes is controlled to be 10%-14%, and the reduction rate of the last four passes is controlled to be 5%-9%. By means of the technical scheme, the problem that in the prior art, the cord thread steel rope is low in wire rope rate is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a control process for homogenizing the structure of high-strength cord steel. Background Art

[0002] In today's industrial field, especially in automobile manufacturing and its supporting industries, the quality and performance of radial tires play a decisive role in the safety, comfort and fuel economy of vehicles. As the core skeleton material of radial tires, the quality of cord steel is of paramount importance.

[0003] With the booming development of the transportation industry, the driving conditions of vehicles are becoming more complex and diverse, and the requirements for tires are becoming increasingly stringent. Not only do they have to carry heavier loads and adapt to the frequent impacts caused by high-speed driving, but they also have to remain stable and reliable under various harsh climate and road conditions. This directly leads to unprecedented performance challenges for cord steel, and traditional cord steel preparation processes are gradually unable to meet market demand.

[0004] For a long time, the industry has faced bottlenecks in terms of uniformity of the cord steel structure. Uneven organizational structures can easily lead to the emergence of stress concentration points, causing the cord steel to bear excessive pressure in local areas when subjected to stress, thereby significantly reducing its strength and toughness. For example, during the high-speed operation of the tire, if the steel cord causes stress concentration due to uneven organization, it is very easy to break, seriously endangering driving safety. At the same time, uneven organization will accelerate the generation and expansion of fatigue cracks, shorten the service life of the tire, and increase the cost of use and maintenance frequency. The level of troostite rate and the uniformity of distribution have an important influence on the uniformity of steel organization. A good troostite rate helps to improve the uniformity of steel organization, thereby improving the comprehensive performance of steel.

[0005] In this context, it is crucial to develop a cord steel preparation process with high organizational uniformity and improve the troostite rate of cord steel. Summary of the invention

[0006] The invention proposes a control process for homogenizing the structure of high-strength cord steel, which solves the problem of low sorbite rate of cord steel in the related art.

[0007] The technical solution of the present invention is as follows: The present invention proposes a control process for homogenizing the structure of high-strength cord steel, comprising the following steps: S1, heating the steel billet to obtain a heat-treated steel billet; S2, rolling the heat-treated steel billet, spinning, and cooling to obtain cord steel; The rolling process includes: 3 to 8 rough rolling passes, 10 to 13 finishing rolling passes, and 2 to 6 sizing passes; During the finish rolling, the reduction rate is controlled at 10% to 14% in the first 5 passes, and the reduction rate is controlled at 5% to 9% in the last 4 passes.

[0008] As a further technical solution, the heating treatment includes a preheating stage, a heating stage, and a soaking stage. The temperature of the preheating stage is 900~950℃, and the time is 15~20min. The temperature of the heating stage is 1050~1200℃, and the time is 30~60min. The temperature of the soaking stage is 1150~1250℃, and the time is 15~20min.

[0009] As a further technical solution, the start temperature of the finishing rolling is 920-940°C, and the final rolling temperature of the finishing rolling is 900-920°C.

[0010] As a further technical solution, the sizing temperature is 890-910°C.

[0011] As a further technical solution, the spinning temperature is 860-870°C.

[0012] As a further technical solution, the cooling rate is 15-25°C / s.

[0013] As a further technical solution, the diameter of the high-strength cord steel is 5.0~6.0mm.

[0014] As a further technical solution, the cord steel is composed of the following elements in percentage by weight: 0.80%~0.85% carbon, 0.1%~0.5% aluminum, 0.3%~0.9% chromium, 1.9%~4.6% manganese, 1.7%~4.9% molybdenum, 0.15%~0.30% silicon, 0.0012%~0.003% phosphorus, 0.0005%~0.004% sulfur, and the balance is iron and unavoidable impurities.

[0015] As a further technical solution, the weight ratio of manganese to molybdenum is 1~2:1.

[0016] In the present invention, the tensile strength of the cord steel is improved by adjusting the weight ratio of manganese to molybdenum to 1-2:1.

[0017] As a further technical solution, the weight ratio of manganese to molybdenum is 1.5:1.

[0018] In the present invention, the weight ratio of manganese to molybdenum is adjusted to 1.5:1, thereby further improving the tensile strength of the cord steel.

[0019] The working principle and beneficial effects of the present invention are: 1. In the present invention, during the heating process, when the steel billet is heated to a suitable temperature, the rolling force required during the rolling process will be significantly reduced, which is beneficial to the long-term stable operation of the rolling equipment and can also improve the rolling efficiency; heating can also improve the quality of steel, by eliminating residual stress and improving the uniformity of the structure, the cord steel finally produced is more excellent, and can effectively reduce the defects inside the steel, such as cracks, uneven structure and other problems, thereby improving the quality and service life of the cord steel.

[0020] 2. In the present invention, rough rolling improves production efficiency. The rough rolling can quickly reduce the size of the steel billet to a suitable range, provide suitable billets for subsequent finishing rolling, and speed up the progress of the entire rolling process.

[0021] 3. In the present invention, the size of the steel after fine rolling can meet the high-precision requirements of the cord steel, which is crucial for manufacturing high-quality cord steel products. In addition, the performance of the steel is significantly improved. The mechanical properties of the steel after grain refinement, such as strength, toughness and ductility, are significantly improved. This enables the cord steel to withstand higher tension and pressure, and is safer and more reliable during use.

[0022] 4. In the present invention, by controlling the reduction rate of the first 5 passes of finishing rolling to 10%-14% and the reduction rate of the last 4 passes of finishing rolling to 5%-9%, the troostite rate of the cord steel is increased and the uniformity of the structure of the cord steel is improved.

[0023] 5. In the present invention, it is convenient to transport and store after spinning. The coiled cord steel occupies less space and is convenient for packaging and transportation. During storage, the coiled form is also easier to manage, which can effectively utilize warehouse space and is conducive to subsequent processing. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A control process for homogenizing high-strength cord steel structure, comprising the following steps: S1, heating the steel billet to obtain a heat-treated steel billet; S2, rolling the steel billet after the heating treatment, spinning, cooling, and obtaining cord steel; The rolling process includes: 8 passes of rough rolling, 13 passes of finishing rolling, and 6 passes of sizing; The reduction rate of each pass during rough rolling, finish rolling and sizing is shown in Table 1.

[0026] The heating treatment includes a preheating stage, a heating stage, and a soaking stage. The temperature of the preheating stage is 950°C for 15 minutes, the temperature of the heating stage is 1200°C for 30 minutes, and the temperature of the soaking stage is 1250°C for 15 minutes. The starting temperature of the finishing rolling is 940℃, and the final rolling temperature of the finishing rolling is 920℃; The temperature for reducing the diameter is 910℃; The spinning temperature is 870℃; The cooling rate is 25℃ / s; The cord steel is composed of the following elements in percentage by weight: 0.85% carbon, 0.5% aluminum, 0.9% chromium, 4.6% manganese, 1.7% molybdenum, 0.30% silicon, 0.003% phosphorus, 0.004% sulfur, and the balance is iron and inevitable impurities.

[0027]

[0028] Example 2 A control process for homogenizing high-strength cord steel structure, comprising the following steps: S1, heating the steel billet to obtain a heat-treated steel billet; S2, rolling the steel billet after the heating treatment, spinning, cooling, and obtaining cord steel; The rolling process includes: 3 roughing passes, 11 finishing passes, and 2 sizing passes; The reduction rate of each pass during rough rolling, finish rolling and sizing is shown in Table 2.

[0029] The heating treatment includes a preheating stage, a heating stage, and a soaking stage. The temperature of the preheating stage is 900°C for 20 minutes, the temperature of the heating stage is 1050°C for 60 minutes, and the temperature of the soaking stage is 1150°C for 20 minutes. The starting temperature of finishing rolling is 950℃, and the final rolling temperature of finishing rolling is 900℃; The temperature for reducing the diameter is 890℃; The spinning temperature is 860℃; The cooling rate is 15℃ / s; The cord steel is composed of the following elements in percentage by weight: 0.80% carbon, 0.1% aluminum, 0.3% chromium, 1.9% manganese, 4.9% molybdenum, 0.15% silicon, 0.0012% phosphorus, 0.0005% sulfur, and the balance is iron and inevitable impurities.

[0030]

[0031] Example 3 A control process for homogenizing high-strength cord steel structure, comprising the following steps: S1, heating the steel billet to obtain a heat-treated steel billet; S2, rolling the steel billet after the heating treatment, spinning, cooling, and obtaining cord steel; The rolling process includes: 5 roughing passes, 12 finishing passes, and 4 sizing passes; The reduction rate of each pass during rough rolling, finish rolling and sizing is shown in Table 3.

[0032] The heating treatment includes a preheating stage, a heating stage, and a soaking stage. The temperature of the preheating stage is 930°C for 18 minutes, the temperature of the heating stage is 1100°C for 45 minutes, and the temperature of the soaking stage is 1200°C for 18 minutes. The starting temperature of the finishing rolling is 930℃, and the final rolling temperature of the finishing rolling is 910℃; The temperature for reducing the diameter is 900℃; The spinning temperature is 865℃; The cooling rate is 20℃ / s; The cord steel is composed of the following elements in percentage by weight: 0.83% carbon, 0.4% aluminum, 0.6% chromium, 2.1% manganese, 3.9% molybdenum, 0.20% silicon, 0.0018% phosphorus, 0.0008% sulfur, and the balance is iron and inevitable impurities.

[0033]

[0034] Example 4 The only difference between this embodiment and embodiment 3 is that the cord steel of this embodiment is composed of the following elements in percentage by weight: 0.83% carbon, 0.4% aluminum, 0.6% chromium, 4.2% manganese, 1.8% molybdenum, 0.20% silicon, 0.0018% phosphorus, 0.0008% sulfur, and the balance is iron and unavoidable impurities.

[0035] Example 5 The only difference between this embodiment and embodiment 3 is that the cord steel of this embodiment is composed of the following elements in percentage by weight: 0.83% carbon, 0.4% aluminum, 0.6% chromium, 3.0% manganese, 3.0% molybdenum, 0.20% silicon, 0.0018% phosphorus, 0.0008% sulfur, and the balance is iron and unavoidable impurities.

[0036] Example 6 The only difference between this embodiment and embodiment 3 is that the cord steel of this embodiment is composed of the following elements in percentage by weight: 0.83% carbon, 0.4% aluminum, 0.6% chromium, 3.6% manganese, 2.4% molybdenum, 0.20% silicon, 0.0018% phosphorus, 0.0008% sulfur, and the balance is iron and unavoidable impurities.

[0037] Example 7 The only difference between this embodiment and embodiment 3 is that the cord steel of this embodiment is composed of the following elements in percentage by weight: 0.83% carbon, 0.4% aluminum, 0.6% chromium, 4.0% manganese, 2.0% molybdenum, 0.20% silicon, 0.0018% phosphorus, 0.0008% sulfur, and the balance is iron and unavoidable impurities.

[0038] Comparative Example 1 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 4.

[0039]

[0040] Comparative Example 2 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 5.

[0041]

[0042] Comparative Example 3 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 6.

[0043]

[0044] Comparative Example 4 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 7.

[0045]

[0046] Comparative Example 5 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 8.

[0047]

[0048] Comparative Example 6 The difference between this comparative example and Example 3 is that the reduction ratio of each pass during rough rolling, finish rolling and sizing in this comparative example is shown in Table 9.

[0049]

[0050] Test Example 1 The volume fraction of troostite in the cord steels prepared in Examples 1 to 3 and Comparative Examples 1 to 6 was tested; the troostite rate was determined by metallographic manual testing in accordance with YB / T 169-2014 "Metallographic Testing Method for Troostite Content in High Carbon Steel Wire Rods", and the results were rounded to one decimal place. The test results are shown in Table 10.

[0051] Table 10 Volume fraction of troostite in cord steel

[0052] Comparing Example 3 with Comparative Examples 1 to 6, it is shown that the reduction ratio of the first 5 passes of finishing rolling is in the range of 10% to 14% and the reduction ratio of the last 4 passes is in the range of 5% to 9%, which can increase the volume fraction of troostite in the cord steel.

[0053] Test Example 2 The cord steels prepared in Examples 1 to 7 were tested as follows: The tensile strength of the cord steel was tested using GB / T 228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method", and the test results are shown in Table 11.

[0054]

[0055] Comparing Examples 5 to 7 with Examples 3 to 4, it is shown that when the weight ratio of manganese to molybdenum is adjusted to 1 to 2:1, the tensile strength of the cord steel is improved; comparing Example 6 with Examples 5 and 7, it is shown that when the weight ratio of manganese to molybdenum is adjusted to 1.5:1, the tensile strength of the cord steel is best improved.

[0056] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A control process for homogenizing high-strength cord steel structure, characterized in that: The following steps are involved: S1, heating the steel billet to obtain a heat-treated steel billet; S2, rolling the heat-treated steel billet, spinning, and cooling to obtain cord steel; The rolling process includes: 3 to 8 rough rolling passes, 10 to 13 finishing rolling passes, and 2 to 6 sizing passes; During the finish rolling, the reduction rate is controlled at 10% to 14% in the first 5 passes, and the reduction rate is controlled at 5% to 9% in the last 4 passes.

2. A control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The heating treatment includes a preheating stage, a heating stage, and a soaking stage. The temperature of the preheating stage is 900-950°C and the time is 15-20 minutes. The temperature of the heating stage is 1050-1200°C and the time is 30-60 minutes. The temperature of the soaking stage is 1150-1250°C and the time is 15-20 minutes.

3. A control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The start temperature of the finishing rolling is 920-940°C, and the final rolling temperature of the finishing rolling is 900-920°C.

4. A control process for homogenizing high-strength cord steel structure according to claim 1, characterized in that: The temperature of the sizing reduction is 890-910°C.

5. The control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The spinning temperature is 860-870°C.

6. A control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The cooling rate is 15-25°C / s.

7. A control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The diameter of the cord steel is 5.0-6.0 mm.

8. The control process for homogenizing the high-strength cord steel structure according to claim 1, characterized in that: The cord steel is composed of the following elements in percentage by weight: 0.80% to 0.85% carbon, 0.1% to 0.5% aluminum, 0.3% to 0.9% chromium, 1.9% to 4.6% manganese, 1.7% to 4.9% molybdenum, 0.15% to 0.30% silicon, 0.0012% to 0.003% phosphorus, 0.0005% to 0.004% sulfur, and the remainder is iron and unavoidable impurities.

9. A control process for homogenizing the high-strength cord steel structure according to claim 8, characterized in that: The weight ratio of manganese to molybdenum is 1-2:

1.

10. A control process for homogenizing the high-strength cord steel structure according to claim 9, characterized in that: The weight ratio of manganese to molybdenum is 1.5:1.